2012
DOI: 10.1007/s13659-012-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

Betanidin significantly reduces blood glucose levels in BALB/c mice fed with an atherogenic diet

Abstract: Abstract:Six weeks BALB/c mice were fed with an atherogenic diet for 24 weeks and purified water ad libitum. An experimental group was given betanidin, orally, during the last 40 days of the experiment at a dose of 9.6 mg per mouse per day. Negative controls were fed with standard rodent chow only. Glycemia was measured at the end of the experiment, after overnight fasting. The group treated with betanidin presented a highly significant reduction of 50.94% compared to positive controls. We conclude that betani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
1
19
1
3
Order By: Relevance
“…The authors contemplated that these observed effects could counter metabolic dysfunctions, because the efficiency, even at very low concentration, was much higher than resveratrol, an approved therapeutic agent (Baur and Sinclair ). Partially supporting the claim of reducing blood glucose levels, betanidin, a red beetroot betalain, was shown to exhibit hypoglycemic effect in mice (Lugo‐Radillo and others ).…”
Section: Dietary Safetymentioning
confidence: 85%
See 2 more Smart Citations
“…The authors contemplated that these observed effects could counter metabolic dysfunctions, because the efficiency, even at very low concentration, was much higher than resveratrol, an approved therapeutic agent (Baur and Sinclair ). Partially supporting the claim of reducing blood glucose levels, betanidin, a red beetroot betalain, was shown to exhibit hypoglycemic effect in mice (Lugo‐Radillo and others ).…”
Section: Dietary Safetymentioning
confidence: 85%
“…Recent studies have reported betalains’ ability to counteract diabetic complications as effects of chronic hyperglycemia. A short report on the hypoglycemic effect of betanidin in mice was published by Lugo‐Radillo and others (). They observed a 50% reduction in the blood sugar levels of mice fed an atherogenic diet (24 wk) when supplemented with betanidin (9.6 mg) for the last 40 d. This study set off a few other investigations on hypoglycemic effect of betalain‐rich preparations or purified betalains.…”
Section: Dietary Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to anthocyanins, betalains have carboxyl functional groups instead of hydroxyl functional groups (Al‐Alwani, Mohamad, Kadhum, & Ludin, ). Betanins possessed a wide range of biological activities as antioxidant, anti‐inflammatory, hypoglycemic, antiproliferative, cardioactive, radioprotective, neuroprotective, diuretic, hypolipidemic, and osteoarthritis pain reliever (Esatbeyoglu et al, ; Khan, ; Lugo‐Radillo, Delgado‐Enciso, & Pena‐Beltrăn, ). The details of their biological activities had been discussed in previous reviews (Gandía‐Herrero, Escribano, & Garcìa‐Carmona, ; Khan, ).…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Areal parts of A. cruentus and A. hybridus contained betacyanin of 40.4 and 6.4 mg amaranthin equivalent/100 g (FW) (Fresh Weight), respectively (Nana, Hilou, Millogo, & Nacoulma, ). Betacyanin is associated with numerous health benefits such as cytotoxic (Khan, ), neuroprotective (Wang & Yang, ), antidiabetic (Lugo‐Radillo, Delgado‐Enciso, & Pena‐Beltrãn, ), and hepatoprotective effects (Lee, Wettasinghe, Bolling, Ji, & Parkin, ).…”
Section: Dietary Phytochemicals In Traditional Leafy Vegetablesmentioning
confidence: 99%